2014
DOI: 10.1016/j.cell.2013.11.031
|View full text |Cite
|
Sign up to set email alerts
|

The N-Terminal Methionine of Cellular Proteins as a Degradation Signal

Abstract: SUMMARY The Arg/N-end rule pathway targets for degradation proteins that bear specific unacetylated N-terminal residues while the Ac/N-end rule pathway targets proteins through their Nα-terminally acetylated (Nt-acetylated) residues. Here we show that Ubr1, the ubiquitin ligase of the Arg/N-end rule pathway, recognizes unacetylated N-terminal methionine if it is followed by a hydrophobic residue. This capability of Ubr1 expands the range of substrates that can be targeted for degradation by the Arg/N-end rule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
205
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 151 publications
(213 citation statements)
references
References 102 publications
(89 reference statements)
4
205
2
Order By: Relevance
“…It was recently shown that both yeast and mammalian Ubr1 can recognize not only the unacetylated primary destabilizing N-terminal residues cited above, but also the unacetylated N-terminal Met residue, if it is followed by a hydrophobic residue. This capability of the Arg/N-end rule pathway greatly expands the range of its substrates, as virtually all nascent proteins bear N-terminal Met (23).…”
Section: Significancementioning
confidence: 99%
See 3 more Smart Citations
“…It was recently shown that both yeast and mammalian Ubr1 can recognize not only the unacetylated primary destabilizing N-terminal residues cited above, but also the unacetylated N-terminal Met residue, if it is followed by a hydrophobic residue. This capability of the Arg/N-end rule pathway greatly expands the range of its substrates, as virtually all nascent proteins bear N-terminal Met (23).…”
Section: Significancementioning
confidence: 99%
“…One of them, called the Arg/N-end rule pathway, targets specific unacetylated N-terminal residues (Fig. 1A) (11,15,23). The primary destabilizing N-terminal residues Arg, Lys, His, Leu, Phe, Tyr, Trp, and Ile are directly recognized by N-recognins.…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, the Arg/N-end rule pathway targets specific un-acetylated N-terminal residues (Arg, Phe, Lys, Leu, His, Tyr, Trp, and Ile) and N-terminal Asn and Gln which have been deaminated and then Arginylated 14 . Un-acetylated N-terminal Met followed by a hydrophobic residue are also targeted for degradation by the Arg/N-end rule pathway 15 . Protein N-terminal acetylation is thought to be relevant to cancer development with NATs acting as tumour suppressors in healthy tissues and oncoproteins in cancerous cells 16 .…”
Section: Introductionmentioning
confidence: 99%